The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1074/jbc.m113.518472
|View full text |Cite
|
Sign up to set email alerts
|

Collapsin Response Mediator Protein 2 (CRMP2) Interacts with N-Methyl-d-aspartate (NMDA) Receptor and Na+/Ca2+ Exchanger and Regulates Their Functional Activity

Abstract: Background: NMDA receptor and Na ϩ /Ca 2ϩ exchanger are involved in glutamate-induced calcium dysregulation in neurons. Results: CRMP2 interacts with and modulates activity of the NMDA receptor and Na ϩ /Ca 2ϩ exchanger. Conclusion: CRMP2 is involved in regulation of Ca 2ϩ homeostasis in neurons exposed to glutamate. Significance: CRMP2 interaction with NMDA receptor and Na ϩ /Ca 2ϩ exchanger affects their activity and is important for glutamate-induced Ca 2ϩ dysregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 48 publications
3
53
0
Order By: Relevance
“…Testing this hypothesis, we recorded NMDAR activity using multielectrode-array recording of RGCs and found that polyarginine compounds do not interfere with NMDA blockade of lightdriven synaptic responses, confirming that the neuroprotection provided by R(7), C-R(7), and CN2097 is not the result of NMDA-receptor antagonism in the intact retina. Supporting this conclusion, it has been reported that Tat does not induce internalization of the NMDA NR2B subunit and the sodium calcium exchanger (NCX) proteins, whereas the neuroprotective peptide Tat-CBD3, a 15-amino acid peptide from CRMP2 fused to Tat, attenuated NMDAR activity and protected neurons against glutamate-induced Ca 2ϩ dysregulation (52). As mitochondria are key players in signaling neuronal death (35,53,54), and with biotin-C-R(7) peptide localizing to mitochondria (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Testing this hypothesis, we recorded NMDAR activity using multielectrode-array recording of RGCs and found that polyarginine compounds do not interfere with NMDA blockade of lightdriven synaptic responses, confirming that the neuroprotection provided by R(7), C-R(7), and CN2097 is not the result of NMDA-receptor antagonism in the intact retina. Supporting this conclusion, it has been reported that Tat does not induce internalization of the NMDA NR2B subunit and the sodium calcium exchanger (NCX) proteins, whereas the neuroprotective peptide Tat-CBD3, a 15-amino acid peptide from CRMP2 fused to Tat, attenuated NMDAR activity and protected neurons against glutamate-induced Ca 2ϩ dysregulation (52). As mitochondria are key players in signaling neuronal death (35,53,54), and with biotin-C-R(7) peptide localizing to mitochondria (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…In many experiments a TAT fused non-arginine containing scrambled peptide (TAT-scramble; TAT-WEAKEMLYFEALVIE; net charge +5) with no amino acid content relationship to the CBD3 peptide was used as a negative control (Brittain et al, 2011a,b;Brustovetsky et al, 2014). In experiments using the TAT-scrambled peptide, negative results similar to the vehicle control were obtained.…”
Section: In Vitro Studiesmentioning
confidence: 92%
“…A further study has also shown that TAT-CBD3 inhibits glutamateand NMDA-induced calcium influx in cultured hippocampal neurons (Brustovetsky et al, 2014), as well as disrupting a CRMP2-NMDA receptor complex interaction, however it did not appear to induce internalisation of the NR2B protein. The same study demonstrated that TAT-CBD3 also inhibits NCX-mediated calcium influx, and that CRMP2 can interact with NCX3 but not with NCX1.…”
Section: In Vitro Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…CRMP2 regulates multiple processes in neurons and was initially discovered to regulate mechanisms of neuronal polarity (9,10). CRMP2 phosphorylation by cyclin-dependent kinase 5 (Cdk5) (11), glycogen synthase kinase 3β (10), Rho-associated protein kinase (12), or the Src-family kinases Fyn (13) and Yes (14) drives its diverse cellular functions, including neurite outgrowth, endocytosis, and ion-channel trafficking (8,(15)(16)(17). Studies of CRMP2 trafficking functions have revealed that CRMP2 facilitates endocytosis of L1-cell adhesion molecule by interacting with the endocytic protein Numb (18) that recruits epidermal growth factor receptor pathway substrate 15 (Eps15), an initiator of clathrin-mediated endocytosis (19).…”
mentioning
confidence: 99%